2022
DOI: 10.1177/17588359221105024
|View full text |Cite|
|
Sign up to set email alerts
|

Network meta-analysis of immune-oncology monotherapy as first-line treatment for advanced non-small-cell lung cancer in patients with PD-L1 expression ⩾50%

Abstract: Background: For patients with advanced non-small-cell lung cancer (NSCLC) and high (⩾50%) programmed cell death-ligand 1 (PD-L1) expression, effective first-line immune-oncology monotherapies with significant survival benefits are approved, cemiplimab being the most recent. In a phase III trial, cemiplimab demonstrated significantly improved overall survival (OS) and progression-free survival (PFS) versus chemotherapy in patients with advanced NSCLC and PD-L1 ⩾50%. A systematic literature review and network me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In a network meta-analysis evaluating PD-(L)1 inhibitors as monotherapy for first-line treatment in NSCLC patients with high PD-L1 expression, researchers identified cemiplimab as the top-ranking agent for OS, followed by atezolizumab and pembrolizumab ( 42 ). In another network meta-analysis assessing immune monotherapy as a first-line treatment for advanced NSCLC patients with PD-L1 expression ≥50%, researchers found that cemiplimab and pembrolizumab exhibited favorable performance in terms of progression-free survival, overall survival, and overall response rate (ORR) ( 44 ). In our current study, cemiplimab also demonstrated favorable performance in OS (HR, 0.48; 95% CI, 0.30–0.77).…”
Section: Discussionmentioning
confidence: 99%
“…In a network meta-analysis evaluating PD-(L)1 inhibitors as monotherapy for first-line treatment in NSCLC patients with high PD-L1 expression, researchers identified cemiplimab as the top-ranking agent for OS, followed by atezolizumab and pembrolizumab ( 42 ). In another network meta-analysis assessing immune monotherapy as a first-line treatment for advanced NSCLC patients with PD-L1 expression ≥50%, researchers found that cemiplimab and pembrolizumab exhibited favorable performance in terms of progression-free survival, overall survival, and overall response rate (ORR) ( 44 ). In our current study, cemiplimab also demonstrated favorable performance in OS (HR, 0.48; 95% CI, 0.30–0.77).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent network meta-analysis of immunotherapies in first-line advanced NSCLC with PD-L1 ≥50% ( 4 ), the base case results comparing EMPOWER-Lung 1 ( 1 ), KEYNOTE-024 ( 5 ), and KEYNOTE-042 ( 6 ) demonstrated cemiplimab was associated with comparable OS and statistically significant improvements in progression-free survival from 6–30 months versus pembrolizumab. No statistically significant differences in the incidence of grade 3–5 adverse events (AEs), grade 3–5 immune-mediated AEs, and all-cause discontinuations due to AEs were observed between the two treatments.…”
Section: Introductionmentioning
confidence: 99%